The moderating of portfolio sustainability impact on oil and gas corporate management resilience in Indonesia - Satria, Ridha; Astarini, Sulfiah Dwi; Utomo, Christiono (Edelweiss Applied Science and Technology, 2025)
In recent volatility, uncertainty, complexity, and ambiguity (VUCA) environments, significant challenges are posed to the business world. Sustainable portfolio governance (SPG) plays a crucial role in enhancing the resilience of project portfolio management offices (PPMOs) to navigate these challenges. However, its application, particularly within the oil and gas (OG) industry, remains underexplored in existing literature. This study aims to address this gap by examining how SPG influences PPMO resilience, with VUCA as a moderating factor. A mixed-methods approach was used, combining a literature review to develop a conceptual framework and a survey to test an empirical model. Data were collected from 112 project management team members in OG companies and analyzed using structural equation modeling (SEM). The results show that SPG significantly enhances PPMO resilience, but VUCA conditions weaken the relationship. These findings underscore the need to formulate strategies to effectively manage VUCA, enabling organizations to quickly adapt to disruptive changes and improve project portfolio outcomes. By addressing these dynamics, this study highlights the critical role of SPG in fostering organizational resilience, particularly in industries that are highly impacted by unpredictable and complex environments such as oil and gas.